2012
DOI: 10.1016/j.cell.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Insulin Resistance: Common Threads and Missing Links

Abstract: Insulin resistance is a complex metabolic disorder that defies a single etiological pathway. Accumulation of ectopic lipid metabolites, activation of the unfolded protein response (UPR) pathway and innate immune pathways have all been implicated in the pathogenesis of insulin resistance. However, these pathways are also closely linked to changes in fatty acid uptake, lipogenesis, and energy expenditure that can impact ectopic lipid deposition. Ultimately, accumulation of specific lipid metabolites (diacylglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
1,527
2
27

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,805 publications
(1,593 citation statements)
references
References 182 publications
(200 reference statements)
37
1,527
2
27
Order By: Relevance
“…Del Aguila, Claffey, and Kirwan (1999) utilized C2C12 cells induced by TNF‐α at a concentration of 10 ng/ml for 1 hr and found that under these conditions, the activity of IRS‐1/2 is inhibited, resulting in a decrease in PI3‐kinase activity and The present study demonstrates inhibition of P42 MARK and P44 MARK phosphorylation, thereby enabling insulin to stimulate the decrease in glucose uptake of C2C12 cells. When TNF‐α binds to its receptor, it activates the JNK pathway and directly inhibits the activity of IRS‐1/2, resulting in the failure of the insulin signaling pathway, leading to cellular IR emergence (Boden et al., 2005; Samuel & Shulman, 2012; Tuncman et al., 2006). Thus, in the present study, a concentration of 10 ng/ml of TNF‐α was also used as a cellular model for the induction of IR in C2C12 cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Del Aguila, Claffey, and Kirwan (1999) utilized C2C12 cells induced by TNF‐α at a concentration of 10 ng/ml for 1 hr and found that under these conditions, the activity of IRS‐1/2 is inhibited, resulting in a decrease in PI3‐kinase activity and The present study demonstrates inhibition of P42 MARK and P44 MARK phosphorylation, thereby enabling insulin to stimulate the decrease in glucose uptake of C2C12 cells. When TNF‐α binds to its receptor, it activates the JNK pathway and directly inhibits the activity of IRS‐1/2, resulting in the failure of the insulin signaling pathway, leading to cellular IR emergence (Boden et al., 2005; Samuel & Shulman, 2012; Tuncman et al., 2006). Thus, in the present study, a concentration of 10 ng/ml of TNF‐α was also used as a cellular model for the induction of IR in C2C12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain homeostasis of blood glucose in the body, pancreatic β cells compensatorily secrete more insulin to elevate the blood insulin level, subsequently contributing to hyperinsulinemia (ADA, 2015; Jiang, Chang, Tai, Chen, & Chuang, 2012; Samuel & Shulman, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, it is the intramyocellular diacylglycerols, 37 not the circulating lipids, that interrupt the insulin signaling and are responsible for insulin resistance progression. Besides, ectopic deposition of lipids in metabolically active organs can induce pathological activation of inflammation 38 , 39 and endoplasmic reticulum stress, 38 , 40 the ability of which to regulate insulin action may be reliant on their ability to alter the levels of key signaling intermediates. 38 It is highly likely that dysregulations of these pathways collectively contribute to insulin resistance.…”
Section: Introductionmentioning
confidence: 99%